2011
DOI: 10.1177/0265659011414214
|View full text |Cite
|
Sign up to set email alerts
|

Communication interventions and their impact on behaviour in the young child: A systematic review

Abstract: Speech, language and communication needs (SLCN) and social, emotional and behaviour difficulties (SEBD) commonly overlap, yet we know relatively little about the mechanism linking the two, specifically to what extent it is possible to reduce behaviour difficulties by targeted communication skills. The EPPI Centre systematic review methodology was applied to the intervention literature related to primary school aged children with both SLCN and SEBD. Studies were graded for study quality. Nineteen studies includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…Research has demonstrated that crucial communication skills improve significantly in children who use SGDs (AAC-RERC, 2011;Drager et al, 2010;Romski, 2005). Furthermore, SGD use is associated with fewer self-injurious or acting out behaviors (Drager et al, 2010;Law, Plunkett, & Stringer, 2012;Light & Drager, 2007). The use of an SGD improves the children's ability to be involved in family life (Granlund, Bjorck-Akesson, Wilder, & Ylven, 2008;Light & McNaughton, 2012;McNaughton & Kennedy, 2010), participate in social situations, and develop social relationships (Beukelman & Mirenda, 2013;Johnston, Reichle, & Evans, 2004;Sellwood, Wood, & Raghavendra, 2012).…”
mentioning
confidence: 99%
“…Research has demonstrated that crucial communication skills improve significantly in children who use SGDs (AAC-RERC, 2011;Drager et al, 2010;Romski, 2005). Furthermore, SGD use is associated with fewer self-injurious or acting out behaviors (Drager et al, 2010;Law, Plunkett, & Stringer, 2012;Light & Drager, 2007). The use of an SGD improves the children's ability to be involved in family life (Granlund, Bjorck-Akesson, Wilder, & Ylven, 2008;Light & McNaughton, 2012;McNaughton & Kennedy, 2010), participate in social situations, and develop social relationships (Beukelman & Mirenda, 2013;Johnston, Reichle, & Evans, 2004;Sellwood, Wood, & Raghavendra, 2012).…”
mentioning
confidence: 99%
“…The ten best evidence studies had 'medium' or 'high' ratings for methodological quality, which is encouraging considering a similar SLR reported difficulties in identifying high quality research (Law et al, 2012). This suggests the availability of evidence-based intervention materials, for example, precision teaching and shared storybook reading to support vocabulary development.…”
Section: Discussionmentioning
confidence: 76%
“…For example, approximately 6% of children have speech, language and/or communication difficulties, of which the majority will not have any other significant developmental problem. Children whose difficulties persist into primary school are likely to experience long-term problems concerning literacy, socialisation, behaviour, and school attainment [8]. Without support, poor communication can impact on a young person’s academic success as well as their social and emotional development, which are all issues of concern in the context of public health [9].…”
Section: Slts’ Contribution To Public Healthmentioning
confidence: 99%
“…This review provides evidence of improvements in behaviour and spontaneous speech and language. In addition, classroom-based co-operative skills programmes have been found to improve expressive and receptive language and social skills [8, 11]. Furthermore, the impact of speech, language and communication interventions as a means to prevent and to reduce social exclusion have been demonstrated in a longitudinal intervention programme delivered to 72 young offenders [12].…”
Section: Slts’ Contribution To Public Healthmentioning
confidence: 99%